Preparation, Spectral Investigation, Thermal Analysis, Biochemical Studying of New (Oxadiazole - Five Membered Ring)- Ligands - Nagham Mahmood Aljamali (Journal of Global Pharma Technology, 2018)
A series of oxadiazole- Azo ligands have been synthesized via many steps sequence. Oxadiazole -azo ligands were prepared through reacting azo–oxadiazole derivatives with phenol heterocyclic derivatives diazotized then coupled via coupling reaction followed by cyclization reaction to yield azo- heterocycles derivatives which act five membered ring. The structures of the newly prepared Ligands were identified through more than technique like (1H NMR, IR and Mass spectra) ,(Thermal ,microbial assay ) for all ligands.Keywords: Oxadiazole, Thiosemicarbazide, Thiadiazol, Cyclization, Azo,Imidazole, Oxazole, Thiazole.